ASSESSMENT OF NUTRITIONAL PROPERTIES OF FERMENTED AND UNFERMENTED SEED OF CISSUS POPULNAE FROM NIGER STATE, NIGERIA - T, Mathew J; N, Dauda B. E; A, Mann; M, Ndamitso M; L, Fadipe A; Y, Shaba E (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The assessment of nutritional properties of fermented (for 24 and 48 h) and unfermented seeds of Cissus populnae from Niger State, Nigeria were determined using standard analytical methods. The proximate parameters determined were moisture, protein, ash, fat, fiber and carbohydrate. The ranges of these values were from 12.44±0.03 (unfermented) to 15.21±0.51 (fermented for 48 h), 4.23±0.16 (unfermented) to 5.04±0.15% (fermentation at 48 h), 2.00±0.05 (unfermented) to 3.10±0.45 (fermented for 48 h), 7.20±0.60 (unfermented) to 9.01±0.11), 4.02±0.23% (fermentation for 48 h) to 7.00±0.06 (unfermented) and 63.62±0.46 (fermented at 48 h) to 67.13±0.53 (unfermented) % for the moisture, crude fiber, ash, crude protein, crude fat and crude carbohydrate contents respectively. The energy values obtained were 1522.61±0.21, 1446.82±0.33 and 1383.45±0.50 Kcal/100g for the unfermented, fermentation for 24 and 48 h respectively. From the results of this study, fermentation generally improved the mineral contents of the samples and decreased their anti-nutrient contents. Thus, large-scale production of fermented Cissus populnae seeds will be a valuable source of nutrition to man and his animals.